THE EFFECT OF WOOD ASHES AND QUAIL DUNG FERTILIZER ON THE GROWTH AND YIELDS OF CAYENNE PEPPER PLANT ON PEAT SOIL - Purwanto, Edy; Hadijah, Siti; Safwan, Mulyadi (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aimed to determine the interaction between wood ashes and quail dung fertilizer as well as the dose of both, which provided the best growth and yield on cayenne pepper in peat soils. The study was conducted at Jl. Equator, Gg. Teluk Betung Maju, Kelurahan Siantan Hilir, Kecamatan Pontianak Utara, Pontianak City. The period of the study by December 3rd 2018 to April 5th 2019. This study used an experimental method with a completely randomized factorial design (CRD) consisting of 2 treatment factors. The first factor was wood ashes with 3 levels of treatment, and the second factor was quail dung manure with 3 levels of treatment. Each treatment was repeated 3 times, each replication consisted of 4 sample plants, so that the total number of plants were 108 plants. The treatment consisted of wood ash treatment i.e a1 = 430 g/polybag equivalent to 21 tons/ha, a2 = 620 g/polybag equivalent to 31 tons/ha, a3 = 810 g/polybag equivalent to 41 tons/ha and fertilizer treatment quail manure enclosure p1 = 200 g/polybag is equivalent to 10 tons/ha, p2 = 400 g/polybag is equivalent to 20 tons/ha, p3 = 600 g/polybag is equivalent to 30 tons/ha. Observation variables in the study were plant height (cm), plant dry weight (g), root volume (cm3), number of productive branches (branches), number of fruits per plant (fruit) and weight of fruits per plant (g). Supporting observation variables on environmental conditions are air temperature ( °C), relative humidity (%) and rainfall (mm). The results of this study showed that interaction of the wood ash treatment and the quail dung manure does not significantly affect all observed variables. The wood ash treatment significantly affected plant dry weight, root volume, number of productive branches, number of fruits per plant and fruit weight per plant but had no significant effect on plant height of 2 MST and 4 MST, while the treatment of quail dung manure no significant effect on all observational variables. The combination of wood ashes at a dose of 810 g/polybag and 400 g/polybag quail dung manure provide the highest rate of yield of cayenne pepper on peat soils.Keywords : wood ash, cayenne pepper, peat, quail dung manure